Dealing With the COVID-19 Infodemic: Distress by Information, Information Avoidance, and Compliance With Preventive Measures - Siebenhaar, Katharina U.; Köther, Anja K.; Alpers, Georg W. (Frontiers in Psychology, 2020)
In the ongoing COVID-19 pandemic, many have experienced anxiety and distress by media reports. Feeling distressed by information may lead to avoidance of information, which has been shown to undermine adherence to preventive health behaviors, such as cancer screenings. We set out to examine whether feeling distressed by information predicts higher avoidance of information about COVID-19 (avoidance hypothesis), and whether this, in turn, predicts worse adherence to measures intended to prevent the spread of COVID-19 (adherence hypothesis). We conducted an online survey (N = 1059) and assessed distress by information (CSS-15-burden subscale), information avoidance, and adherence to preventive behaviors. Furthermore, we inquired about participants’ information seeking behavior and media usage, trust in media sources, level of eHealth literacy (eHEALS), and generalized anxiety (GAD-7). We conducted multiple linear regression analyses for hypothesis testing and to examine what variables predicted distress by information. Also, we explored the role of trust in media sources and eHealth literacy. Supporting our hypotheses, higher distress by information predicted more information avoidance (avoidance hypothesis), and information avoidance predicted worse adherence to preventive measures (adherence hypothesis). Moreover, individuals with higher eHealth literacy reported higher trust in the media sources used, less distress by information, and less information avoidance. These findings provide insights into the consequences of distress by information and avoidance of information during a global health crisis. Results imply that information avoidance may be a maladaptive response to distress by information, which may go on to interfere with effective crisis management. We emphasize the need to develop measures to counteract information avoidance.